Improving Toothbrushing Skills Through the Use of Animated Video Media for Students with Mild Mental Retardation - Kurnia, Muhammad Fadlan; Efrina, Elsa; Ardisal; Budi, Setia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study discusses the use of animated video media in tooth-brushing instruction for students with mild intellectual disabilities at the Al- Azra'iyah Koto Baru Simalanggang Special Needs School. The purpose of this study was to improve the tooth-brushing skills of students with mild intellectual disabilities. The main objective of this study is that students with mild intellectual disabilities are not yet able to understand the steps for brushing their teeth properly, correctly, and sequentially. This study used a classroom action research method because it aimed to improve outcomes and systematically refine the learning process through designed actions. This study was conducted in two cycles, including planning, implementation, observation, and reflection. After the actions were administered in cycle I, results showed a slight increase in the tooth-brushing skills of students with mild intellectual disabilities, but these actions did not produce the expected results. After reflecting on cycle I, the study continued to cycle II. Only after the actions were administered in cycle II did the expected results be achieved.